Wallit - Isaacs, Andrew; Schaefer, Kristin (London : SAGE Publications Ltd, 2017)
Wallit is a service platform that provides location-based virtual "walls" on which people can write via their smart phones, but only when they are near that wall. Wallit creates virtual walls along streets, in shopping malls, on or inside buildings, or in any other location. Individuals can write to the wall, put picture and video to the wall, view others postings, click on links posted to the wall, and interact with the wall using their phones camera. Wallit is an app company with a growing number of wall locations around the world in landmarks, popular locations along streets, shopping malls, on or inside buildings or sporting stadiums, etc. Wallit hoped to become the new means by which people will share their experience digitally at any location. The company has received funding by well-known venture capitalists and angels in Silicon Valley and its first product was launched through the Apple AppStore in early 2012, followed by a version for the Android platform in the Android market. The Wallit case study outlines the company's key decision points as it readies for launching the company and product in 2012. The key questions relate to which applications to focus on and what target market(s) to focus on.
Originally published: Isaacs, A., & Schaefer, K. (2012). Wallit. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wallit; Marketing -- Case studies; Social media -- Case studies